ANALISIS SISTEM DRAINASE MENGGUNAKAN HEC-RAS DI KABUPATEN JEPARA - hidayati, nor; Prasetiyo, Bayu; Rochmanto, Decky; malana, zidnal; amalia, alfina; Laura, Yesenia; sutiyono, Sutiyono (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
This research aims to: (1) determine the drainage water storage capacity along Jalan Raya Bangsri–Keling Km 02, Wedelan, Bangsri District, Jepara Regency; (2) identify the factors causing flooding in the study area; and (3) propose appropriate alternative solutions for flood mitigation based on existing site conditions. Data were collected through field surveys, primary and secondary data acquisition, and analysis of existing data. Hydraulic analysis was conducted using HEC-RAS software. The results indicate that the existing drainage system in Wedelan Village has a maximum discharge capacity of 0.45 m³/s (equivalent to 450 L/s), which is insufficient to accommodate the calculated peak discharge of 0.83 m³/s (830 L/s). Therefore, a new drainage channel design is proposed with dimensions of B = 1.0 m and H = 1.2 m.